Determinants Of Export Performance: Export Business Model, External Environment And Government Assistance Of Malaysian Processed Food And Beverage Sme Manufacturers - Nor, Aidi Zulkarnain Md (2018)
Malaysia as a small size economy, requires international trade to ensure sustainable economic growth as it can no longer rely on domestic demand to drive its economy. Currently, Malaysia is the fourth country in the world relying heavily on international trade. Moving forward, the Government of Malaysia has embarked on a New Economic Model to transition the country into an advanced and developed nation which recognized SMEs as the engine for export growth of manufactured goods. Despite the significant role played by SMEs, the current export contribution of Malaysian SMEs is still at the discouraging state and SMEs should start planning a more efficient business model. However, there are still deficiencies of knowledge about business model concept as determinants of SMEs export performance in the current literature review. The purpose of the present research is to investigate empirically the effects of firm export business model, external environment and export assistance provide by government agencies on firm export performance, thus offers new insights for the nature of export performance determinants. The theoretical foundations of the resource-based view (RBV), business model view (BMV), structure conduct performance (SCP) paradigm and institutional theory (INT) provide fundamental understanding on the research variables and their relationship with export performance. This research employs mixed-method exploratory sequential design which include phase one qualitative approach (i.e., exploratory) that utilizes an in-depth interview on a non-probability purposive sampling of five respondents (organization) and phase two quantitative approach (i.e., explanatory) that utilizes a cross-sectional online survey questionnaire on a non-probability census sampling of 142 Malaysian processed food and beverage SME manufacturers to fulfill the research agenda. The present research applies hierarchical component modeling (HCM) approach to capture theoretical framework and utilised PLS-SEM using SmartPLS 3.0 software for statistical analysis. The results revealed that firm export business model construct exhibit a highly statistically significant positive effect on the firm export performance, suggesting that the business model concept is a strong determinant of firm export performance. However, other variables such as external environment and government assistance as moderator exhibit non-significant results. Theoretically, the present research reinforces the empirical test of RBV logic by suggesting new insights that business model concept as a form of determinants of export performance. Methodologically, when the present research setting examines the net effect of a combination resources, capabilities and business process in the context of firms’ export business model components, the present research succeeded in measuring business model concept as a net effect of a combinations of export business model components using type II reflective-formative HCM of PLS-SEM approach rather than measuring in a single export business model component. Practically, the present research able to (1) map the existing Malaysian processed food and beverage SME manufacturers business model; (2) identify four important business model components for the industry (i.e., partnership [business network], value proposition [standardization], customer relationship [personalize], and customer segment [mass market segment]), and (3) identify strength and weaknesses in the existing Malaysian processed food and beverage SME manufacturers business model. Those theoretical, methodological and practical implications thus contribute to the new knowledge on determinants of SMEs export performance.